WORK–FAMILY CONFLICT, WORK–LIFE BALANCE, AND JOB SATISFACTION AS PREDICTORS OF NURSES’ INTENTION TO STAY: A LITERATURE REVIEW - Aswin Wikantama; Burhannudin Ichsan; Muzakar Isa (Jurnal Medika: Medika, 2025)
The purpose of this literature review is to explore and synthesize empirical evidence regarding the influence of work–family conflict, work–life balance, and job satisfaction on nurses’ intention to stay in hospital settings. A narrative review approach was employed, gathering studies from Scopus, PubMed, and Google Scholar. From an initial pool of 267 articles, 35 met the inclusion criteria, which focused on nurses, hospital-based contexts, and methodological clarity. The findings reveal that work–family conflict negatively affects both work–life balance and job satisfaction, which in turn lowers the intention to stay. Conversely, work–life balance and job satisfaction serve as critical mediators that can buffer the negative impact of role conflict on workforce retention. The review is framed by Role Stress Theory and Social Exchange Theory to explain the dynamic relationships among variables. These findings underscore the importance of organizational support mechanisms, such as flexible work arrangements, performance recognition, and psychological well-being programs, to improve nurses’ motivation and long-term retention. In conclusion, promoting positive work–life interaction and enhancing job satisfaction are essential strategies for sustaining a stable nursing workforce in hospital environments, particularly in high-demand and resource-limited healthcare systems.